PENGARUH CELEBRITY ENDORSER SLANK TERHADAP MINAT BERDONASI MASYARAKAT PADA ORGANISASI NON-PROFIT PROFAUNA - Yoshua Glennardo (Parsimonia - Jurnal Ekonomi dan Bisnis, 2018)
Celebrity endorser usually promotes only commercial products, it rarely promotes non profit organization cause. The purpose of this research is to find out the influence of celebrity endorser, SLANK, towards the public interest in making donation to non profit organization, PROFAUNA (Protection of Forest & Fauna). From the so many celebrities that support PROFAUNA, SLANK is chosen because it has the biggest number of fans. Online questionaire was used to collect the data using non probability sampling technique. Characteristics of the respondents are that they know about PROFAUNA and SLANK. Sample size is 200 respondents. Partial Least Square (PLS) was used to analyzed the collected data. The main results are that SLANK as celebrity endorser has 15% positive influence on public interest to make donation to PROFAUNA with the dominant celebrity endorser dimension of 0.584.